Evaluate to improve: useful approaches to student evaluation. Issue 1 (2nd January 2016) - Golding, Clinton; Adam, Lee
Abstract : Many teachers in higher education use feedback from students to evaluate their teaching, but only some use these evaluations to improve their teaching. One important factor that makes the difference is the teacher's approach to their evaluations. In this article, we identify some useful approaches for improving teaching. We conducted focus groups with award-winning university teachers who use student evaluations to improve their teaching, and we identified how they approach their evaluation data. We found that these teachers take a reflective approach, aiming for constant improvement, and see their evaluation data as formative feedback, useful for improving learning outcomes for their students. We summarise this as the improvement approach, and we offer it for other teachers to emulate. We argue that if teachers take this reflective, formative, student-centred approach, they can also use student evaluations to improve their teaching, and this approach should be fostered by institutions to encourage more teachers to use student evaluations to improve their teaching.